2012
DOI: 10.1002/ejic.201201121
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Spin Crossover in the Polymeric Material [Fe(Htrz)2(trz)](BF4) Including Coherent‐Domain Size Reduction Effects

Abstract: The high‐spin and low‐spin crystal structures of [Fe(Htrz)2(trz)](BF4) (Htrz = 1H‐1,2,4‐triazole, trz– = deprotonated triazolato ligand) were determined and refined on the basis of X‐ray diffraction data obtained from a high‐quality crystalline powder. Noteworthy differences to the previously reported structural hypothesis are obtained, which includes a revision of the space group to orthorhombic Pnma. Notably, the distinction between the positions of the Htrz and the trz– ligand along the chains reveals their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 22 publications
11
145
0
Order By: Relevance
“…A Rietveld refinement was performed for each one on the basis of the atomic positions previously derived from their crystal structures. [14] These refinements first confirmed that these samples all have the same crystallographic structure. The sole difference observed between their diffractograms is the width of the Bragg peaks.…”
Section: Isotropic Viewmentioning
confidence: 69%
See 1 more Smart Citation
“…A Rietveld refinement was performed for each one on the basis of the atomic positions previously derived from their crystal structures. [14] These refinements first confirmed that these samples all have the same crystallographic structure. The sole difference observed between their diffractograms is the width of the Bragg peaks.…”
Section: Isotropic Viewmentioning
confidence: 69%
“…The structural investigation of [Fe(Htrz) 2 (trz)](BF 4 ) was limited until the recent determination of its crystal structure by means of X-ray diffraction. [14] The crystal packing is based on infinite [Fe(Htrz) 2 (trz)] + chains linked together through interactions mediated by the anions and hydrogen bonding. This SCO material shows the largest known volume expansion (ca.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] If this mechanical strain is efficiently transferred to the electroactive polymer matrix a change of the polarization level of this latter should take place due to the electro-mechanical coupling. Under short-circuit conditions one would therefore expect a transient current flow during the spin transition.…”
mentioning
confidence: 99%
“…However, reaching the transition temperature, an abrupt increase of the refraction index is observed with SCO induced change of refraction index estimated at Δn/n ~ 6%. This cannot be explained via the density change related to SCO (d LS  = 1.98 g cm −3 , d HS  = 1.778 g cm −3 )37, which decreases about 11% during the transition from LS to HS states, whereas with SCO the refraction index of 1 increases.…”
Section: Resultsmentioning
confidence: 93%